Perancangan Aplikasi Penyewaan Peralatan Pendakian Berbasis Android Pada Polahi Adventure - Citra Yustitya Gobel; Muhammad Isla; Ifriandi Labolo; Satiadi D Ali (Himpunan Dosen Gemilang Indonesia (HDGI), 2024)
One of the business models that is developing now is doing business through Android-based smartphone applications. Android is a new generation of mobile platform, a platform that gives developers the ability to develop according to their expectations. So many business people are switching to Android applications, including the climbing equipment rental business. The problem in this research is that the community, especially prospective climbers, currently still have difficulty finding information on renting climbing equipment and Polahi Adventure still has problems in the process of collecting data on incoming and outgoing equipment because all transactions are carried out using books, so it takes time and is less effective. in the reporting process. The design of an Android smartphone-based climbing equipment rental application can provide equipment and ordering information to users, especially prospective climbers, with various features in the application, namely equipment features, chart features for rental applications and chat features for communicating with Polahi Adventure. The development method used is the waterfall system development method, which includes the stages of needs analysis, system design, implementation, testing and maintenance. This application is designed with main features such as searching and ordering equipment, real-time stock management, order status notifications, and an integrated payment system. Test results show that this application is able to increase the efficiency of the rental process, make it easier for users to make orders, and provide accurate information regarding equipment availability. This application not only makes it easier for customers to rent climbing equipment, but also helps Polahi Adventure manage its business more effectively and efficiently. This research ends with the conclusion that the application developed can be well received by users and has the potential to be developed further by adding additional features according to market needs.